Opposite evolution in incidence of Crohn's disease and ulcerative colitis in Northern France (1988–1999). Issue 6 (11th May 2004) - Molinié, F; Gower-Rousseau, C; Yzet, T; Merle, V; Grandbastien, B; Marti, R; Lerebours, E; Dupas, J-L; Colombel, J-F; Salomez, J-L; Cortot, A
Abstract : Background: Northern France was characterised by a high incidence of Crohn's disease (CD) and a low incidence of ulcerative colitis (UC) according to the first inquiry undertaken in the late 1980s. Aims: To assess the trends in the incidence of inflammatory bowel disease (IBD) over a 12 year period (1988–1999) in the same area of Northern France. Patients: Patients living in Northern France (Nord, Pas-de-Calais, Somme, and Seine Maritime—total of 5 790 526 inhabitants) between 1988 and 1999 were included in the study. Case ascertainment was established according to methodology previously described. Methods: Trends in incidence were studied using a Poisson regression model in four three year periods (1988–90, 1991–93, 1994–96, and 1997–99) adjusted for age at diagnosis and sex. Incidence rates were standardised for age with the European standard population. Results: During 1988–99, 7066 cases of IBD were recorded (56.8% CD, 37.7% UC, and 5.5% indeterminate colitis). Mean annual incidence rate of CD increased from 5.2/100 000 inhabitants in 1988–90 to 6.4 in 1997–99 (adjusted p for trend <0.001). In contrast, the incidence of UC decreased from 4.2 to 3.5 (adjusted p for trend <0.001). The ileocolonic subtype of CD increased by 25% even though median age at diagnosis and frequency of digestive investigations were not different. Conclusions: Contrary to what has been reported in other countries in Northern Europe, the incidence of CD increased by 23% in 12 years in Northern France while that of UC decreased by 17% during the same period. This indicates that some factors which influence IBD frequency (in both directions) are still at work in this area of Europe, and that further studies aimed at identifying these should be performed. The rising incidence of CD could enhance the burden of this disease on the public health system in France.